Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.6 - Special Products - Exercise Set - Page 387: 29



Work Step by Step

$(2x-1)^{2}$ Apply the formula for squaring a binomial, which is $(a-b)^{2}=a^{2}-2ab+b^{2}$ Here, $a=2x$ and $b=1$ $(2x-1)^{2}=(2x)^{2}-2(2x)(1)+1^{2}=4x^{2}-4x+1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.